PO161 Catastrophic arachnoiditis following posterior fossa aneurysmal subarachnoid haemorrhage. (1st December 2017) - Zarkali, Angeliki; Kumar, Guru; Crocker, Matthew; Flores, Lorena; Harikrishnan, Sreedharan
Abstract : Arachnoiditis is a rare complication of subarachnoid haemorrhage (SAH) with less than 30 cases reported. It commonly presents following a posterior fossa aneurysm, with haemomyelia being the proposed trigger of inflammatory response.We present a case and review the literature. A 55 year old right-handed carpenter, presented with three week history of sudden onset band-like thoracic chest pain, followed by progressive numbness and weakness of both legs and micturition difficulty. Three months prior, he had a spontaneous SAH secondary to two posterior inferior cerebellar artery aneurysms;these were clipped and he made a complete recovery. Examination showed myelopathy with a T9 sensory level and urgent MRI showed extensive arachnoiditis of the cervical, thoracic and lumbar spine with cauda equina compression. He was transferred to a neurosurgical unit and had an attempted laminectomy and drain insertion; weakness worsened significantly post-operatively. Two courses of IV methylprednisolone had no effect and he was left with spastic paraplegia, incontinence and T6 sensory level. Post-SAH arachnoiditis is rare, with no consistent approach to treatment and variable outcomes; commonly following posterior fossa aneurysms. Clinical suspicion in patients presenting with myelopathy post-SAH may lead to earlier recognition and treatment. Unfortunately, in our patient, neither surgery or immunomodulation affected disease progression.